Binding Between Cyclohexanohemicucurbit[n]urils and Polar Organic Guests - Ustrnul, Lukas; Burankova, Tatsiana; Öeren, Mario; Juhhimenko, Kristina; Ilmarinen, Jenni; Siilak, Kristjan; Mishra, Kamini A.; Aav, Riina (Frontiers in Chemistry, 2021)
Inherently chiral, barrel-shaped, macrocyclic hosts cyclohexanohemicucurbit[n]urils (cycHC[n]) bind zinc porphyrins and trifluoroacetic acid externally in halogenated solvents. In the current study, we tested a set of eighteen organic guests with various functional groups and polarity, namely thiophenols, phenols, carboxylic and sulfonic acids, to identify a preference towards hydrogen bond donating molecules for homologous cycHC[6] and cycHC[8]. Guests were characterized by Hirshfeld partial charges on the acidic hydrogens and their binding by 1H and 19F NMR titrations. Evaluation of association constants revealed the complexity of the system and indirectly proved external binding with stoichiometry over 2:1 for both homologs. It was found that overall binding strength is influenced by the stoichiometry of the formed complexes, the partial atomic charge on the hydrogen atom of the hydrogen bond donor, and the bulkiness of the guest. Additionally, a study on the formation of complexes with halogen anions (Cl−, Br−) in methanol and chloroform, analyzed by 1H NMR, did not confirm complexation. The current study widens the scope of potential applications for host molecules by demonstrating the formation of hydrogen-bonded complexes with multisite hydrogen-bond acceptors cycHC[6] and cycHC[8].